Development of the Rheumatoid Arthritis Symptom Questionnaire (RASQ): a patient reported outcome scale for measuring symptoms of rheumatoid arthritis. (2nd September 2017) - Banderas, Benjamin; Skup, Martha; Shields, Alan L.; Mazar, Iyar; Ganguli, Arijit
Abstract: Background: Rheumatoid arthritis (RA), a chronic, progressive inflammatory, autoimmune disease, can substantially reduce health-related quality of life (HRQoL) and lead to severe disability and early mortality. Patient-reported outcome (PRO) instruments are used to assess the patient experience of RA symptoms and impacts, and can capture RA treatment effects. To address limitations in existing PRO instruments, this research aimed to establish the content validity of a new instrument, the Rheumatoid Arthritis Symptom Questionnaire (RASQ), to assess the signs and symptoms of RA. Method: The most important and relevant sign and symptom concepts for RA patients were identified through a targeted review of the published literature, expert opinion, and concept elicitation patient interviews. Cognitive interviews were conducted with patients to test the comprehensibility and comprehensiveness of the RASQ. Results: Seven symptoms emerged consistently across the conceptual research: joint pain, joint swelling, joint stiffness, joint tenderness, joint warmth, muscle pain, and tiredness. Draft item content was developed to assess these symptoms, in addition to a single impact item, resulting in three RASQ versions: two utilizing a 7 day recall period (one assessing symptoms at their worst, the other on average) and a third using a 24 hour recall period assessing symptoms at their worst. Cognitive interview results demonstrated patient understanding and ability to use the instrument. Conclusions: Content validity of the RASQ was established in accordance with instrument development guidelines. The RASQ fills a measurement gap by assessing the RA signs and symptoms most important to patients. Research evaluating the RASQ's psychometric properties is underway.